2021
DOI: 10.1177/03000605211005878
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of cancer antigen 125 before hormone replacement therapy are not associated with clinical outcome of frozen embryo transfer in women with adenomyosis

Abstract: Aim This retrospective study aimed to evaluate the predictive value of serum cancer antigen 125 (CA125) levels before hormone replacement therapy on pregnancy outcomes in women with adenomyosis undergoing frozen embryo transfer. Methods A total of 509 women with adenomyosis were screened and 84 patients receiving a total of 114 cycles of frozen embryo transfer were included, based on the inclusion and exclusion criteria. Patients were divided into two groups based on their CA125 levels (≤ or >35 IU/mL) befo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In this study, the mean CA-125 concentration in the pregnant group and the non-pregnant group did not differ, with p > 0.05. According to a study by Ling Huang (2021) conducted on 84 infertile patients with adenomyosis, there was no association between CA-125 levels and pregnancy outcomes [20]. Similarly, KE Fish (2004) also found that CA-125 levels had no value in predicting pregnancy outcomes (AUC = 0.63) [21].…”
Section: Some Related Factors Affecting the Outcome Of Ivf In Inferti...mentioning
confidence: 99%
“…In this study, the mean CA-125 concentration in the pregnant group and the non-pregnant group did not differ, with p > 0.05. According to a study by Ling Huang (2021) conducted on 84 infertile patients with adenomyosis, there was no association between CA-125 levels and pregnancy outcomes [20]. Similarly, KE Fish (2004) also found that CA-125 levels had no value in predicting pregnancy outcomes (AUC = 0.63) [21].…”
Section: Some Related Factors Affecting the Outcome Of Ivf In Inferti...mentioning
confidence: 99%
“…[2][3][4][5][6] However, there is no accepted biomarker, related to inflammatory mediators, for strategy decision in adenomyosis. 7 CA125 is a high macromolecule glycoprotein, increasingly secreting from the embryonic coelomic epithelium to serum by peritoneal irritation or peritoneal stretch in an inflammatory microenviroment. 8 CA125 is best known as a marker of epithelial ovarian cancer; nevertheless, CA125 levels can also be elevated in a number of relatively benign gynecologic conditions, such as endometriosis, adenomyosis, endometriosis, and uterine fibroids.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the distribution and quantification of CA125 in the mechanism of dysmenorrhea is not clear. 7 We retrospectively analyzed the data from a cohort of patients before focused ultrasound ablation surgery (FUAS), aiming to explore the association between CA125 and dysmenorrhea in adenomyosis, to validate the cut-point of CA125 of 35 U/mL for dysmenorrhea in adenomyosis, and to investigate the factors contributing to the elevated CA125 level in adenomyosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations